Effect of Thickness on Electrical and Optical Properties of ZnO:Al Films - Chanthong, Thawatchai; Intaratat, Weerawat; Na Wichean, Thanate (Trends in Sciences, 2023)
Zinc oxide (ZnO:Al) films were prepared on a substrate of different thicknesses by sputtering at 1×10−2 mbar argon gas pressure and 200 W power. The effect of film thickness on the structural, electrical, and optical properties was investigated by X-ray diffraction (XRD), 4-point probe technique, and ultraviolet-visible spectroscopy. The XRD film crystal structure study revealed that all sample films at thicknesses of 66, 106, 150 and 193 nm, respectively, exhibited planar Hexagonal wurtzite crystal structure (002), and ZnO crystals were grown along the c-axis. The ZnO:Al film at a thickness of 66 nm had the highest strain and the smallest crystal size compared to other films. The electrical resistivity decreases with increasing film thickness. The sample at 193 nm has the lowest resistivity (1.37 Ω.m). The results showed that light transmission revealed that all sample films had high transparency in the white and near-UV region at a wavelength of 350 to 800 nm, with an average light transmittance shift of 85 - 95 %. The energy band gap increased with the film thickness of 3.49(66 nm), 3.55(106 nm), and 3.59(150 nm) eV, and decreased to 3.57 eV at 193 nm, respectively. HIGHLIGHTS The different thicknesses Zinc oxide (ZnO:Al) films were prepared by sputtering at 1×10-2 mbar argon gas pressure and 200 W power was used to study the effect of film thickness on the structural, electrical, and optical properties The electrical resistivity changing of ZnO:Al film depends on the film thickness. The electrical resistivity is reduced with increasing ZnO:Al film thickness The ZnO:Al film are highlighted by their characteristics for light transmission at the wavelengths between 350 and 800 nm, and exhibited exceptional transparency in the white and near-UV range GRAPHICAL ABSTRACT